2021
DOI: 10.3390/ijms22189997
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XV Promotes ER Stress-Induced Inflammation through Activating Integrin β1/FAK Signaling Pathway and M1 Macrophage Polarization in Adipose Tissue

Abstract: Collagen XV (Col XV), a basement membrane (BM) component, is highly expressed in adipose tissue, and studies have found that Col XV is related to extracellular matrix (ECM) remodeling involving in adipose tissue fibrosis and inflammation. Furthermore, the ECM is essential for maintaining normal development and tissue function. In this study, we found that Col XV is related to the endoplasmic reticulum stress (ERS) and inflammation of adipose tissue. Moreover, we found that overexpression of Col XV in mice coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…18 Adipose ECM remodeling is always associated with increased macrophage infiltration and upregulation of adipose tissue inflammation. 18,38,39 Generally, inflammatory factors in the microenvironment can recruit macrophages that secrete MMPs, which in turn degrade the ECM. 40,41 Our results showed that, over time, the number of nucleated cells in the graft gradually increased from the periphery to the center, and on the third day after transplantation, there were already M1-macrophage infiltrating the periphery of the graft and subsequently migrated gradually toward the center of the graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Adipose ECM remodeling is always associated with increased macrophage infiltration and upregulation of adipose tissue inflammation. 18,38,39 Generally, inflammatory factors in the microenvironment can recruit macrophages that secrete MMPs, which in turn degrade the ECM. 40,41 Our results showed that, over time, the number of nucleated cells in the graft gradually increased from the periphery to the center, and on the third day after transplantation, there were already M1-macrophage infiltrating the periphery of the graft and subsequently migrated gradually toward the center of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…In the fat transplantation model, the grafted ECM is disrupted and undergoes remodeling in the post‐transplantation period 18 . Adipose ECM remodeling is always associated with increased macrophage infiltration and upregulation of adipose tissue inflammation 18,38,39 . Generally, inflammatory factors in the microenvironment can recruit macrophages that secrete MMPs, which in turn degrade the ECM 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The topic “Translation from Microgravity Research to Earth Application” comprises publications focusing on space life sciences, gravitational biology and space medicine [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. It covers publications reporting the impact of altered environmental conditions, such as microgravity (µ g ), cosmic radiation and isolation on organisms down to the level of cells [ 3 , 4 , 5 , 7 , 8 , 10 , 11 , 12 , 13 , 14 ].…”
mentioning
confidence: 99%
“…The topic “Translation from Microgravity Research to Earth Application” comprises publications focusing on space life sciences, gravitational biology and space medicine [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. It covers publications reporting the impact of altered environmental conditions, such as microgravity (µ g ), cosmic radiation and isolation on organisms down to the level of cells [ 3 , 4 , 5 , 7 , 8 , 10 , 11 , 12 , 13 , 14 ]. In addition, the topic collects studies validating causal diagrams of human health risks for spaceflight [ 1 ], hypergravity studies [ 2 ] and investigations about the impact of extreme isolation in the Antarctica on the human body [ 6 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation